2019
DOI: 10.1186/s12960-019-0351-y
|View full text |Cite
|
Sign up to set email alerts
|

Never again? Challenges in transforming the health workforce landscape in post-Ebola West Africa

Abstract: Background The 2013–2014 West African Ebola outbreak highlighted how the world’s weakest health systems threaten global health security and heralded huge support for their recovery. All three Ebola-affected countries had large shortfalls and maldistribution in their health workforce before the crisis, which were made worse by the epidemic. This paper analyzes the investment plans in Liberia, Sierra Leone, and Guinea to strengthen their health workforces and assesses their potential contribution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Overall, the main strengths of member states and the region for that matter include: in country capacity to test; strong political support; the existence of incident management systems (IMS) and rapid response teams (RRTs) that are on alert for activation, the availability of three tiers of skilled eld epidemiology workforce, the availability of experienced public health practitioners able to adopt existing and new preparedness and response protocols to country-speci c contexts; and their readiness to collaborate on cross-border surveillance and response. These strengths represent modest gains in health system resilience of the ECOWAS region as envisaged by WAHO and development partners following some investments in region (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the main strengths of member states and the region for that matter include: in country capacity to test; strong political support; the existence of incident management systems (IMS) and rapid response teams (RRTs) that are on alert for activation, the availability of three tiers of skilled eld epidemiology workforce, the availability of experienced public health practitioners able to adopt existing and new preparedness and response protocols to country-speci c contexts; and their readiness to collaborate on cross-border surveillance and response. These strengths represent modest gains in health system resilience of the ECOWAS region as envisaged by WAHO and development partners following some investments in region (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Second, from a global health perspective, this financial support served to implement policies such as raising epidemic awareness which could reduce the perceived risk felt by Western citizens 36. McPake et al in their estimates of fiscal space projections in West African Ebola-affected countries report a declining projection (6%) of total health expenditures between 2020 and 2030 in Guinea 37. This suggests that policy actors in the MoH should develop strategies to overcome this situation which may impede the achievement or sustainability of the current GHS goals 37.…”
Section: Discussionmentioning
confidence: 99%
“…McPake et al in their estimates of fiscal space projections in West African Ebola-affected countries report a declining projection (6%) of total health expenditures between 2020 and 2030 in Guinea 37. This suggests that policy actors in the MoH should develop strategies to overcome this situation which may impede the achievement or sustainability of the current GHS goals 37. Therefore, they should prioritise efficiency management of HCWs by decentralising recruitment, removing ghost workers and communicating effectively on the outcomes of HSS on health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…universal mental health provision through a psychiatricallytrained cadre of health workers unfeasible to attain within the foreseeable future (Bah et al, 2018;McPake et al, 2019).…”
Section: Status Of Mental Health Provisionmentioning
confidence: 99%
“…A roll-out of Psychological First Aid training for primary healthcare workers (Sijbrandij et al ., 2020) has lacked the follow-up that research has indicated is required to sustain a major uplift in capacity in this setting (Horn et al ., 2019). In combination, a lack of sustained funding and a severe shortage of healthcare personnel renders universal mental health provision through a psychiatrically-trained cadre of health workers unfeasible to attain within the foreseeable future (Bah et al ., 2018; McPake et al ., 2019).…”
Section: Understanding Mental Health In Sierra Leonementioning
confidence: 99%